1985
DOI: 10.1128/jvi.56.1.183-193.1985
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation in vitro of Escherichia coli-produced 235R and 266R tumor antigens encoded by human adenovirus type 12 early transformation region 1A

Abstract: The tumor (T) antigens encoded by the human adenovirus early transforming region 1A (ElA) are gene regulatory proteins whose functions can immortalize cells. We have recently described the synthesis in Escherichia coli and the purification of the complete T antigens encoded by the adenovirus type 12 (Adl2) ElA 12S mRNA (235-residue [235R] T antigen) and 13S mRNA (266R T antigen). In this study, we show that the Adl2 ElA T antigens are extensively phosphorylated in Adl2-infected mammalian cells but are not phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…We also compared the relative mobilities of in vitro-and in vivo-32 P-labeled E1A and found them to be indistinguishable by SDS-PAGE (data not shown), which is consistent with previous results (65).…”
Section: Time Course Of the Phosphorylation Of E1a In Vitrosupporting
confidence: 90%
“…We also compared the relative mobilities of in vitro-and in vivo-32 P-labeled E1A and found them to be indistinguishable by SDS-PAGE (data not shown), which is consistent with previous results (65).…”
Section: Time Course Of the Phosphorylation Of E1a In Vitrosupporting
confidence: 90%
“…Evidence is also presented here that this major site of ElA phosphorylation is not phosphorylated by cAMP-dependent protein kinases. Data supporting both of these conclusions come from the results of Lucher et al (33). They used a partially purified protein kinase from uninfected human KB cells to phosphorylate in vitro Adl2 ElA proteins synthesized in Escherichia coli.…”
Section: Discussionmentioning
confidence: 90%
“…It should be noted that these previous studies were done with crude ammonium sulfate fractions from liver, and the results reported here are for the purified recombinant enzymes expressed in E. coli . Moreover, rat liver GNMT is phosphorylated, while the recombinant enzymes expressed in E. coli probably are not 27. It is not known what effect this post‐translational modification has on the kinetics of GNMT.…”
Section: Resultsmentioning
confidence: 99%